1996
DOI: 10.1051/aas:1996232
|View full text |Cite
|
Sign up to set email alerts
|

Fractional abundances of molecules in dense interstellar clouds: A compendium of recent model results

Abstract: Abstract. -In this paper we present calculated fractional abundances in dense interstellar clouds for selected atomic and molecular species using three different homogeneous, pseudo-time-dependent models discussed by Bettens, Lee, & Herbst (1995): the new standard model, the new neutral-neutral model, and model 4. We have run each model with 3 different hydrogen densities -10 3 , 10 4 , and 10 5 cm −3 -and two temperatures -10 K and 50 K. "Low metal" elemental abundances have been used for all three models; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(207 citation statements)
references
References 31 publications
10
194
1
Order By: Relevance
“…When these complex molecules are dissociated by the strong UV fields of M 82, their abundances decrease, while a similar decrease for CH 3 CCH is balanced by ion molecule reactions favoring its formation. On the other hand, a strong anti correlation between N CH3CCH and T kin has been observed in galactic sources (Lee et al 1996), and the gas in M 82 is indeed as cold as ∼30 K. Methyl acetylene is not observed in the regions of densities < 10 5 cm −3 since it would be dissociated, but in regions of intermediate densities (Region II), where it is well shielded from the dissociating radiation. Furthermore, we do not see it in the Region I, presumably because its abundance in such places is almost negligible, although it could exist there (Chrurchwell & Hollis 1983).…”
Section: Evolved Starburst: M 82mentioning
confidence: 98%
“…When these complex molecules are dissociated by the strong UV fields of M 82, their abundances decrease, while a similar decrease for CH 3 CCH is balanced by ion molecule reactions favoring its formation. On the other hand, a strong anti correlation between N CH3CCH and T kin has been observed in galactic sources (Lee et al 1996), and the gas in M 82 is indeed as cold as ∼30 K. Methyl acetylene is not observed in the regions of densities < 10 5 cm −3 since it would be dissociated, but in regions of intermediate densities (Region II), where it is well shielded from the dissociating radiation. Furthermore, we do not see it in the Region I, presumably because its abundance in such places is almost negligible, although it could exist there (Chrurchwell & Hollis 1983).…”
Section: Evolved Starburst: M 82mentioning
confidence: 98%
“…The initial chemical abundances used for the Horsehead PDR (Lee et al 1996a;Morata & Herbst 2008) are listed in Table 2 and represent abundances for a dark cloud prior to the onset of a nearby star. These abundances comprise observed values for small (less-than-six-atom) species in TMC-1, as well as calculated early-time values from Smith et al (2004) for atoms and small molecules that have not been observed, based on socalled "low-metal" elemental abundances.…”
Section: Physical Conditions and Initial Chemical Abundancesmentioning
confidence: 99%
“…where k HD is the rate coefficient of reaction 3 (see below), Oliveira et al 2003), k CO = 3.3 × 10 −9 (T/10 K) −0.5 cm 3 s −1 is the rate coefficient of the reaction H 2 D + + CO → products, k N 2 = 1.7 × 10 −9 cm 3 s −1 is the rate coefficient for the reaction Lee et al 1996), k e = 5.5 × 10 −7 (T/10 K) −0.65 cm 3 s −1 is the dissociative recombination rate of H 2 D + (see Caselli et al 1998), and k gr is the rate of recombination of H 2 D + on negatively charged dust grains, which, following Draine & Sutin (1987), is given by:…”
Section: A Simple Analytical Modelmentioning
confidence: 99%